TEACHING DERIVATIONAL PROCESS TO COMPOSE PROPER SENTENCE - Efransyah - efransyah (Eltin Journal : Journal of English Language Teaching in Indonesia, 2019)
The title of this research is Teaching Derivational Process to Compose Proper Sentence. The objective of this study was to prove whether or not that Teaching Derivational Process influences students’ ability in using the proper words in constructing proper sentence. The group pre-test post-test design and quantitative method were used in this research. There were 26 students in this research to be entire population and they are from SMK Mohammad Toha Cimahi. This research used pre-test and post-test as the instruments. The data were collected by giving the instruments to the students, both pre-test (before giving the students treatment) and post-test (after giving the students treatment) and to analyze the data, the writer used t-test formula. The result of this study showed that  the mean score of pre-test was 50,38, the mean score of post-test was 82,30, the t-obs was 10, 96, the t-table with degrees of freedom (df) was 25 and level significance at 5 % (0,05) was 1,71. From the data analysis, the writer concluded that the students’ understanding about derivational process influenced their ability in using the proper word in constructing proper sentence and it also meant that the t-observe was higher than t-table (10,96 > 1,71), so the alternative hypothesis was accepted.